Assessing the instructional processes in higher education institutions: Amhara region’s universities and colleges in focus - Tadesse Melesse Merawi (Bahir Dar Journal of Education)
This study assessed the instructional processes of Universities and Colleges of the Amhara Region, Ethiopia. The research design was descriptive survey and data were obtained from 204 participants (instructors, department heads and deans from Universities and Colleges) using questionnaire, interview and focus group discussion. Both University and College instructors’ practices of the instructional processes and their conceptions on effective teaching and the factors affecting effective teaching were examined. Results indicated that the three interactive instructional processes (instructional planning, methods of teaching and assessment) were not adequately implemented in an integrated manner. More specifically, significant differences were observed between Universities and Colleges in the application of instructional planning and continuous assessment (assessment for learning that served as a feedback for students’ learning). In this regard, Colleges were in a good position than Universities. However, active learning strategies that could enhance higher order thinking and problem-solving skills of students were not applied passably in both the Universities and the Colleges. There was also no statistically significant difference among the three Universities and the three Colleges themselves in applying various active learning methods. Attitudinal problems to prepare instructional plans (mainly for Universities), lack of knowledge on various active learning strategies and work load were influencing factors for the effective implementation of the instructional processes in Universities and Colleges. As a result, re-conceptualizing the practices of instructional processes in Universities and Colleges to enhance effective teaching is a timely concern for all education actors at various levels.